2004
DOI: 10.3136/fstr.10.25
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Super Chilling Storage on Maintenance of Freshness of Kuruma Prawn

Abstract: Using natural prawn (Penaeus japonicus), a comparison study was conducted between super chilling (؊2˚C) and cool (5˚C) storage for the effectiveness of keeping fish meat fresh. Brightness of the tail color could be retained longer using super chilling storage compared to traditional refrigeration. In addition, a significant color difference in a values between the two methods was confirmed when a colorimeter was used. As a physical property of the meat, significant softening was observed after 2 days refrigera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 20 publications
3
30
0
Order By: Relevance
“…However, the prevalence of L. monocytogenes and organoleptic properties were higher after 28 days at superchilling, followed by 28 days in chilling, compared to samples stored at superchilling/ chilling for 14 days before chilling for 28 days. During superchilled storage of kuruma prawn, the brightness of the tail colour could be retained compared to traditional refrigeration where unfavorable changes in quality such as discoloration, deterioration of texture and a rapid rise in the amount of inosine and hypoxanthine in relation to the total amount of ATP and substances derived from ATP (K-value) were found (Ando et al, 2004). On evaluating the impact of superchilling on the quality of pre-rigour Atlantic salmon (Salmo salar) fillets, Bahuaud et al (2008) found that superchilling prevented the fillets from rigour contraction.…”
Section: Quality Aspects In Relation To Superchilling Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…However, the prevalence of L. monocytogenes and organoleptic properties were higher after 28 days at superchilling, followed by 28 days in chilling, compared to samples stored at superchilling/ chilling for 14 days before chilling for 28 days. During superchilled storage of kuruma prawn, the brightness of the tail colour could be retained compared to traditional refrigeration where unfavorable changes in quality such as discoloration, deterioration of texture and a rapid rise in the amount of inosine and hypoxanthine in relation to the total amount of ATP and substances derived from ATP (K-value) were found (Ando et al, 2004). On evaluating the impact of superchilling on the quality of pre-rigour Atlantic salmon (Salmo salar) fillets, Bahuaud et al (2008) found that superchilling prevented the fillets from rigour contraction.…”
Section: Quality Aspects In Relation To Superchilling Methodsmentioning
confidence: 98%
“…The initial freezing points of most foods are between À0.5°C and À2.8°C (Duun and Rustad, 2007). Ando et al (2004) defined superchilling as the temperature zone below 0°C but where ice crystals are not generated. Beaufort et al (2009) defined superchilling as a technology where food is stored just below the initial freezing temperature.…”
Section: Superchillingmentioning
confidence: 99%
“…Lu et al (2013) found that super chilling storage could extend the shelf life of Songpu mirror carp (Cyprinus carpio) by 12 days compared with chilled storage. Ando et al (2004) reported that super chilling storage was able to maintain the color of prawns and the physical properties of the meat, and consequently offered potential as a new storage technique suitable for replacing refrigeration. Claussen (2011) suggested that super chilling enable safe, high quality and long term storage of foods.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies have focused on the chemical, microbiology and physical analyses of foods in superchilling (Bahuaud et al 2008;Beaufort et al 2009;Duun andRustad 2007, 2008;Erikson et al 2011;Gallart-Jornet et al 2007;Ando et al 2004;Bao et al 2007). Very few studies show the relationship between ice crystals development and quality of food during superchilled storage.…”
Section: Introductionmentioning
confidence: 99%